Cholesterol accumulation in hepatocytes mediates IRE1/p38 branch of endoplasmic reticulum stress to promote nonalcoholic steatohepatitis - SÖZEN, AHMET ERDİ (My University, 2022)
Non-alcoholic fatty liver disease (NAFLD), based on the elevating obesity incidence, is one of the major health issue worldwide. Transition from NAFLD to non-alcoholic steatohepatitis (NASH) is driven by increased apoptosis and is relevant to higher morbidity rates. In regard to limited understanding on cholesterol mediated hepatocyte alterations in NALFD/NASH transition, we investigated endoplasmic reticulum (ER) stress and related apoptosis. Our findings suggest that cholesterol upregulates ER stress and enhances C/EBP homologous protein (CHOP) either in hypercholesterolemic rabbits or in hepatocytes treated with liposome-cholesterol complex. Mechanistically, cholesterol accumulation in hepatocytes activates IRE1/p38 branch of ER stress, stimulating CHOP levels. In liver tissues of cholesterol fed rabbits, α-tocopherol supplementation decreased IRE1/p38/CHOP activation and prevented NASH development. Thus, our study provides a critical role of hepatocyte cholesterol in inducing IRE1/p38/CHOP pathway and suggests novel candidates for therapeutic targets against NASH.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); İlaç Keşfi; Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Yapısal Biyoloji; Moleküler Biyoloji; Endokrinoloji; Klinik Biyokimya; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Structural Biology; Molecular Biology; Endocrinology; Clinical Biochemistry; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Cholesterol; NASH; Endoplasmic reticulum stress; Apoptosis; ?-Tocopherol; FATTY LIVER-DISEASE; SYNERGISTIC INTERACTION; DIETARY-CHOLESTEROL; PROTEIN-KINASES; OXYSTEROLS; APOPTOSIS; OBESE; ACTIVATION; INJURY; ACIDS; Cholesterol; NASH; Endoplasmic reticulum stress; Apoptosis; α-Tocopherol